Adequacy of herniated disc tissue as a cell source for nucleus pulposus regeneration: laboratory investigation - Hegewald, Aldemar Andres; Endres, Michaela; Abbushi, Alexander; Cabraja, Mario; Woiciechowsky, Christian; Schmieder, Kirsten; Kaps, Christian; Thomé, Claudius (Journal of neurosurgery. Spine, 2011)
Object: The object of this study was to characterize the regenerative potential of cells isolated from herniated disc tissue obtained during microdiscectomy. The acquired data could help to evaluate the feasibility of these cells for autologous disc cell transplantation. Methods: From each of 5 patients (mean age 45 years), tissue from the nucleus pulposus compartment as well as from herniated disc was obtained separately during microdiscectomy of symptomatic herniated lumbar discs. Cells were isolated, and in vitro cell expansion for cells from herniated disc tissue was accomplished using human serum and fibroblast growth factor-2. For 3D culture, expanded cells were loaded in a fibrin-hyaluronan solution on polyglycolic acid scaffolds for 2 weeks. The formation of disc tissue was documented by histological staining of the extracellular matrix as well as by gene expression analysis of typical disc marker genes. Results: Cells isolated from herniated disc tissue showed significant signs of dedifferentiation and degeneration in comparison with cells from tissue of the nucleus compartment. With in vitro cell expansion, further dedifferentiation with distinct suppression of major matrix molecules, such as aggrecan and Type II collagen, was observed. Unlike in previous reports of cells from the nucleus compartment, the cells from herniated disc tissue showed only a weak redifferentiation process in 3D culture. However, propidium iodide/fluorescein diacetate staining documented that 3D assembly of these cells in polyglycolic acid scaffolds allows prolonged culture and high viability. Conclusions: Study results suggested a very limited regenerative potential for cells harvested from herniated disc tissue. Further research on 2 major aspects in patient selection is suggested before conducting reasonable clinical trials in this matter: 1) diagnostic strategies to predict the regenerative potential of harvested cells at a radiological or cell biology level, and 2) clinical assessment strategies to elucidate the metabolic state of the targeted disc.
Gesehen am 28.09.2022